2018
DOI: 10.1186/s40360-018-0239-9
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating effect of imidacloprid on arsenic-induced testicular toxicity in Wistar rats

Abstract: BackgroundIt is an established fact that humans and animals are exposed to more than one chemical concurrently from various sources such as food, air and water. In the past, much emphasis was laid on evaluating the toxic effects of a single chemical. Nowadays an increased attention is being paid to the interaction of xenobiotics with one another. Therefore, a study was aimed to evaluate the potentiating effect of imidacloprid (IMI) on arsenic-induced testicular toxicity in rats.MethodsAdult male Wistar rats ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Co-exposure to IMI and arsenic produced more pronounced fall in TTH level (63.8%) in renal tissue as compared to control ( Table 1 ). Similar decline in TTH level have also been reported in different visceral organs in arsenic exposed rats [ [46] , [47] , [48] ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Co-exposure to IMI and arsenic produced more pronounced fall in TTH level (63.8%) in renal tissue as compared to control ( Table 1 ). Similar decline in TTH level have also been reported in different visceral organs in arsenic exposed rats [ [46] , [47] , [48] ].…”
Section: Resultssupporting
confidence: 84%
“…The reduction in activities of these antioxidant enzymes might be either due to increased concentration of free radicals or decreased concentration of reduced glutathione a substrate for different antioxidant enzymes like GPx, GST and GR. Such pronounced alterations in different antioxidant parameters in different visceral organs of animals exposed concurrently to insecticides and metals have been reported [ 41 , [46] , [47] , [48] ].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Protein and nonprotein thiols are critical components of the antioxidant defence systems that are actively involved in the protection of important organelles through their ability to scavenge free radicals and/or provide the substrate for the enzymatic antioxidants including the superoxide dismutase and glutathione peroxidase which were also conserved, in this study, in rats treated with AF1 following sodium arsenite exposure. Exposure to Arsenic compounds has been associated with reduced level of thiols in testicular tissue of rats with consequent aggravation of oxidative stress‐mediated injury in testicular tissues (Mahajan, Verma, Raina, & Shilpa, 2018). Exposure to sodium arsenite has been reported to cause cellular cytotoxicity and downregulation of the antioxidant defence system by inducing oxidative stress in Leydig and Sertoli cells (Yilmaz, Yildizbayrak, & Erkan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In polycystic ovary syndrome study, it has been observed that native thiol, total thiol, disulphide levels in the ovary tissues of patients with polycystic ovary syndrome do not change compared to the control group [148]. It has been determined that arsenic and imidocarb reduce the total thiol level in the testicular tissue of rats with testicular damage [149]. In a study, it was concluded that chemotherapeutic agents cause ovarian damage in women and that the reduction of thiol level is very important in the mechanism of this damage [150].…”
Section: Thiol Status In Reproductive System Diseasesmentioning
confidence: 99%